Investigation of a new integrated system for multiple outputs with hydrogen and methanol - Acar, Canan; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
In this study, an integrated multigeneration system that can produce hydrogen, electricity, heat, and methanol simultaneously is thermodynamically investigated. This integrated multigeneration system consists of three subsystems, namely: (i) electrolyzer, (ii) thermal power plant; and (iii) methanol production reactor. Energy and exergy analyses of all system components, as well as the sustainability analysis of the whole system, is performed thoroughly. The integrated system's thermodynamic performance is thoroughly investigated by changing some critical operational and environmental parameters in parametric studies. Based on the results of this study, recommendations for better energetic, exergetic, and environmental performance are presented for better sustainability. The results of this study show that the integrated multigeneration system is capable of producing hydrogen, heat, electricity, and methanol with overall energetic and exergetic efficiencies about 68% and 47%, respectively. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Methanol; Energy; Exergy; Efficiency; Sustainability; COMBINED HEAT; CO2 HYDROGENATION; ENERGY SOLUTIONS; POWER; ELECTRICITY; DESIGN; OXIDE; Chemistry; Electrochemistry; Energy & Fuels